Verbal Teachings in Thai Literature of Phra Aphai Mani - รินปัญโญ, อำภาพร; พูลพิพัฒน์, นราวัลย์; พันชนะ, กรรณิการ์ (Ganesha Journal, 2019)
The objectives of this research were to investigate hortatory discourse in the Thai literary work, Phra Apai Mani, and to examine Buddhist teachings in the literary work by analyzing the work in volumes 1-4, written by Sunthon Phu, the Fine Arts Department version, published in 2001. The analysis results are present descriptively and critically based on the study’s analysis framework, together with the author’s opinions in an attempt to answer the study objectives. The study results are summarized as follows. The use of hortatory discourse in the literary work consists of four domains, namely, appropriate conduct, teaching or education, entertainment or satisfaction, and presentation or persuasion. The Buddhist teachings found in the literary work, volumes 1, 3 and 4, are composed of nine spiritual perfections. They include generosity: giving without expecting anything in return; moral discipline: maintaining one’s body and speech within the moral framework; renunciation: being ordained to study Buddhist teachings; wisdom: using knowledge to carefully prepare and plan for one’s work; energetic effort: being perseverant and brave; patient endurance: enduring difficulties, anger and dissatisfactoriness; truthfulness: being determined and sincere to commit oneself to work; determination: fixing and settling a purpose and asking for blessing; and loving kindness: loving, helping and supporting other humans and animals. For volume 2, the exhortative discourse and Buddhist teachings contain only two kinds of spiritual perfections. They include loving kindness: loving, wishing or supporting all sentient beings to become happy and prosperous; and wisdom: being knowledgeable, insightful and reasonable to understand natural states of things as they truly are.